Excellent long-term results with minimally invasive edge-to-edge repair in myxomatous degenerative mitral valve regurgitation. (28th March 2020) - Belluschi, Igor; Lapenna, Elisabetta; Blasio, Andrea; Del Forno, Benedetto; Giacomini, Andrea; Ruggeri, Stefania; Schiavi, Davide; Castiglioni, Alessandro; Alfieri, Ottavio; De Bonis, Michele
Abstract: OBJECTIVES: Previous series of minimally invasive mitral valve repairs showed excellent results at up to 10 years of follow-up. The goal of this study was to assess the long-term durability beyond 10 years of the edge-to-edge repair for myxomatous degeneration performed through a minimally invasive approach. METHODS: Ninety-seven consecutive patients (mean age 35 ± 9 years; left ventricular ejection fraction 63 ± 6%) with severe myxomatous mitral regurgitation (MR) underwent mitral valve repair through a right minithoracotomy between 1999 and 2006. MR was due to lesions involving the posterior leaflet (7.2% of patients), anterior leaflet (12.4%) and both leaflets (80.4%). RESULTS: No hospital deaths occurred. At hospital discharge all patients had no or trivial MR. Follow-up was 100% complete (median 15.5 years; interquartile range 13.6–17.0, max 19.3 years). The 16-year overall survival rate was 95.9 ± 2.02% [95% confidence interval (CI) 89.39–98.43]. At 16 years, the cumulative incidence function of cardiac death, with non-cardiac death as a competing risk, was 3.1 ± 1.75 (95% CI 0.83–8.02). Only 3 patients (4.1%) had redo operations for recurrent severe MR. At 16 years, the cumulative incidence functions of reoperation for and recurrence of MR ≥3+, with death as a competing risk, were 3.1 ± 1.76% (95% CI 0.83–8.02) and 5.6 ± 2.47% (95% CI 2.06–11.83), respectively. No predictors of recurrence of MR ≥3+ were identified. At the last follow-up, moderate MR (2+/4+) was detected in 17 patients (17.5%); most of the patients were in New York Heart Association functional class I–II (97%) and in sinus rhythm (90%). CONCLUSIONS: Minimally invasive mitral valve edge-to-edge repair through a right minithoracotomy for myxomatous degeneration appears to be an effective and durable approach even in the long-term follow-up (up to 19 years).